The “Opusmusiuum - Roman Mosaics in Portugal” Academic Project: from Teachers’ Lab to Public - Filomena LIMÃO (Journal of Mosaic Research, 2018)
This paper will briefly describe an online academic project about Roman mosaics in Portugal created by students and a teacher during the Spring Semester 2011 at the Faculty of Social Sciences and Humanities, NOVA University, Lisbon. The project is titled “Opusmusiuum- Roman Mosaics in Portugal” and just as the muses have inspired the work of mosaics, students were enthusiastically involved in making their idea come to light i.e. preparing quality information about Roman mosaics found in Portugal either in situ or in museums for a website catalogue. The contents would be displayed to students, researchers and lay public through short videos, audio recordings and short texts. Eventually, this website would fulfil a gap in the specialized Portuguese literature on this topic. On June 2011, Professor José Maria Blázquez Martínez attended the V. International Symposium of the Mosaic Corpus of Türkiye in Kahramanmaraş, Turkey, where a group of Portuguese and Spanish researchers met. His enthusiasm for the potentialities of the study of mosaics and the joy for new discoveries have always motivated students and colleagues to continue investigation. In Kahramanmaraş, his inspiring example made me think about academia as an exciting place were ideas are born and shared, a challenging environment I would call, a “teachers’ lab.” The “Opusmusiuum- Roman Mosaics in Portugal” project was the result of a teachers’ lab and now that seven years have passed since it was devised in a classroom I think that its goals, achievements (though incomplete) and values of good scientific practice are worthy of paying tribute to an inspiring Professor. Like Professor Blázquez, we persevere in this task hoping one day the Opusmusiuum will meet its public.